(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
English functions as a global means of communication, resulting in the development of several pronunciation standards. Among these, American-based pronunciation standards, commonly represented by General American English, occupy a central position in international communication, education, and media. This article examines the defining phonetic characteristics of American-based pronunciation, including rhoticity, vowel quality, consonant realization, stress patterns, and intonation. It also discusses the role of American pronunciation in language teaching and mass media, as well as its advantages and limitations in the context of global English usage. The study highlights the importance of understanding American-based pronunciation as a widely intelligible and influential model of spoken English.